Participatory forest management and its impacts on livelihoods and forest status: the case of Bonga forest in Ethiopia - Gobeze, T.; Bekele, M.; Lemenih, H.; Kassa, H. (2009)
The forest resources in Ethiopia have suffered decades of mismanagement due mainly to loosely defined property relations over these resources. As one of the solutions, Participatory Forest Management (PFM) scheme was introduced during the early 1990s by some NGOs. Nearly two decades of experience now exists in the country. However systematic assessments of the performance of the scheme are scanty. This study reports the experience from Bonga PFM project, which is one of the oldest pilot sites. Forest inventory and socio-economic survey were conducted to collect data. The study was conducted during a transition from NGO - Community to State - Community based management of the PFM project. PFM is shown to have positive impacts both on the state of the forest and living condition of participant households at least within the project life time. Forest conditions such as seedling and sapling densities improved. PFM also (i) promoted awareness about forest, (ii) capacitated locals to form new institutional arrangement that increased their participation in forest management, helped to reduce open access and assisted a regulated forest use, and (iii) contributed towards social equity in terms of gender and minority ethnic groups. When accompanied with complementary non-forest based livelihood activities, PFM helped to diversify income sources, increase household income level, and build household assets. This reduced dependence of communities on forests for livelihoods. A challenge threatening the sustainability of the PFM program in Ethiopia is the weak government support for the scheme. PFM is still far from being mainstreamed in the forest management system of the country. Thus, it will be appropriate to assess how the PFM programs would perform few years after the support of the NGOs terminates.